Evaluation of the Effects of Bariatric Surgery in Terms of Weight Loss and Diabetes Remission in the Indian Population - Manish Khaitan (Karger Publishers, 2021)
Objectives: The growing prevalence of obesity rates worldwide is associated with an upsurge in its comorbidities, particularly type 2 diabetes mellitus (T2DM). Bariatric surgery is a proven treatment modality for producing sustained weight loss and resolution of associated T2DM providing marked improvement in quality of life with rapid recovery. This study aims to investigate the effects of laparoscopic sleeve gastrectomy (LSG), Roux-en-Y gastric bypass (RYGB), and mini-gastric bypass (MGB) on obese patients suffering from T2DM in the Indian population and their long-term association with regard to diabetes remission, resolution of comorbidities, and percentage EWL. Methods: Retrospective data of obese patients with T2DM (preoperative BMI 45.37 ± 8.1) who underwent bariatric surgery (RYGB, LSG, and MGB) were analyzed in this study over a period of 9 years. The mean follow-up period was 2.2 years. Following surgery, the clinical outcome on BMI, resolution of percentage weight loss, and T2DM were studied. The predictive factors of diabetic remission after surgery were determined. Student’s t test and ANOVA and McNemar’s test were applied. Results: Out of a total of 274 patients, complete remission of T2DM was achieved in 52.9% (n = 145) with mean fasting blood glucose and glycated hemoglobin values being 6.1 ± 0.769 (p = 0.00) at 1 year after surgery. The independent predictive factors of remission were age, gender, BMI, preoperative comorbidities, and % EWL. Gender had no correlation with the chance of achieving disease remission. Conclusion: Based on our results, bariatric surgery proves to be a successful treatment option resulting in sustained weight loss in obese patients suffering from T2DM. It is found to be beneficial for the long-term resolution of T2DM and improving comorbidities such as hypertension and dyslipidemia. The outcome of the different surgical methods is found to be similar for all patients irrespective of the independent predictors of complete remission.